3-/3,5-Styryl-Substituted BODIPY with N-Bridged Annulation: Synthesis and Spectroscopic Properties - Chang, Le; Zhou, Shengjie; Kong, Xiangduo; Gai, Lizhi; Lu, Hua (Synthesis, 2024)
The development of organic dyes with high fluorescence quantum yield (FLQY) and tunable emission has significant application potential in biomedicine and material science. The synthesis of four N-bridged annulated BODIPY dyes with styryl units at the 3- and 3,5-positions of the BODIPY core, introduced by Knoevenagel condensation reaction, is reported. These dyes show high FLQY and tunable fluorescence. The intrinsic relationship between structure and properties is comprehensively analyzed through density functional theory (DFT) calculations, which is crucial for the rational design of new BODIPY dyes with desired properties for specific applications.
Keywords: BODIPY; N-bridged annulation; Knoevenagel condensation reaction; Cadogan reaction; TD-DFT calculation